Effects of Jian Pi Qu Shi Formula on intestinal bacterial flora in patients with idiopathic membranous nephropathy: A prospective randomized controlled trial. Issue 2 (1st June 2020) - Lang, Rui; Wang, Xin‐Hui; Li, Ai‐Feng; Liang, Ying; Zhu, Bao‐Chen; Shi, Bin; Zheng, Yong‐Qiu; Yu, Ren‐Huan
Abstract: Background: The incidence of idiopathic membranous nephropathy (IMN) has recently increased remarkably. Immune dysfunction caused by disordered intestinal flora might be an important factor affecting IMN. The Jian Pi Qu Shi Formula (JPQSF) shows promise in treating IMN. Here, we sequenced 16S rRNA genes to compare intestinal flora between patients with IMN and healthy persons. We also conducted a randomized controlled clinical trial to further compare the intestinal flora of patients with IMN treated with traditional Chinese medicine (TCM) and western medicine (WM). Methods: Among 40 patients with IMN treated at Department of Nephrology in Xiyuan Hospital, Chinese Academy of Traditional Chinese Medicine between July 2016 and December 2018, we compared 30 of them with 10 healthy persons (controls). The IMN group was randomly assigned to receive JPQSF (TCM) or immunosuppressant WM therapy in ( n  = 15 per group) for 6 months. Intestinal microbiota diversity was analyzed using alpha diversity and beta diversity. Intestinal flora that significantly differed between the groups was analyzed using MetaStat. The effects and safety of the therapies were determined based on the values for plasma albumin, 24‐h urine protein excretion, serum creatinine, urea nitrogen, estimate glomerular filtration rate (eGFR), complete blood count, and liver enzymes. All data were statistically analyzed using Statistical Package for the Social Sciences (SPSS) 20.0 statistical software. Results: Baseline characteristics did not significantly differ between the IMN and healthy groups, or the TCM and WM groups. After six months of treatment, 24‐h urinary protein significantly declined in the TCM and WM groups (before and after treatment: 3.24 ± 1.74 vs. 1.73 ± 1.85 g, P  < 0.05 and 3.94 ± 1.05 vs. 1.91 ± 1.18 g, P  < 0.05, respectively). Plasma albumin was significantly increased in the TCM group (before vs. after treatment: 32.44 ± 9.04 vs. 39.99 ± 7.03 g/L, P  < 0.05), but did not significantly change in the WM group (31.55 ± 4.23 vs. 34.83 ± 9.14 g/L, P >  0.05). Values for urea nitrogen, serum creatinine, and eGFR did not significantly change in either group. The alpha diversity index for intestinal flora differed between the IMN and healthy groups, and the TCM and WM groups. Comparisons of multiple samples (beta diversity) revealed differences in intestinal flora between the IMN and healthy groups, and the TCM and WM groups. The Metastat analysis findings showed that the main genera that differed between the IMN group before treatment and the healthy group were Christensenellaceae_R‐7_group, Bifidobacterium (77), Dorea, Escherichia‐Shigella, Parabacteroides, Bifidobacterium, and Coprococcus_3. After TCM therapy, the main differential genera were Butyricimonas, Bacteroides, Alistipes, and Lachnospira, and after WM therapy, these were Ruminococcus_2, Lachnospiraceae_ND3007_group, Lachnospira, Bifidobacterium, Alistipes, and [Eubacterium]_ventriosum_group. Conclusion: Patients with IMN might have disordered intestinal flora, and JPQSF can regulate intestinal flora in patients with IMN.